2012
DOI: 10.1093/molbev/mss253
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Adapts to a Changing Stressful Environment by Evolving Cross-Protection and Anticipatory Gene Regulation

Abstract: Organisms can protect themselves against future environmental change. An example is cross-protection, where physiological adaptation against a present environmental stressor can protect an organism against a future stressor. Another is anticipation, where an organism uses information about its present environment to trigger gene expression and other physiological changes adaptive in future environments. "Predictive" abilities like this exist in organisms that have been exposed to periodic changes in environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 88 publications
2
74
0
1
Order By: Relevance
“…S1, Supplementary Material online). The use of a neutral environmental cue (here caffeine) is important as it helps to differentiate AP from other evolutionary adaptations influenced by cross-protection (Dhar et al 2013), where resistance to one stress has components that confer increased resistance to a second unrelated stress. 5-FOA is converted by orotidine 5′-phosphate decarboxylase (Ura3) into 5-fluorouracil, which is toxic to the cell (Boeke et al 1984) (supplementary fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1, Supplementary Material online). The use of a neutral environmental cue (here caffeine) is important as it helps to differentiate AP from other evolutionary adaptations influenced by cross-protection (Dhar et al 2013), where resistance to one stress has components that confer increased resistance to a second unrelated stress. 5-FOA is converted by orotidine 5′-phosphate decarboxylase (Ura3) into 5-fluorouracil, which is toxic to the cell (Boeke et al 1984) (supplementary fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such adaptive mechanisms are expected to evolve as a long-term strategy, but the rate of evolution of anticipatory gene regulation remains to be measured. In an attempt to do this, Dhar et al [26] evolved yeast populations under fluctuating conditions of oxidative and salt stress during 300 generations [26]. An asymmetric cross-protection or anticipation evolved where oxidative stress protects against salt stress but not the opposite.…”
Section: Mechanisms Of Anticipation and Memory (A) Anticipation And Amentioning
confidence: 99%
“…Such changes include fluctuation in temperature or nutrient levels (Tagkopoulos et al 2008; Van der Linden et al 2010), and seasonality is an ubiquitous driver of fluctuating selection in organisms with generation times of a month or less (Messer et al 2016). A few mechanisms have been identified that can help organisms to prepare for recurring stressors (Dhar et al 2013), for example, bet hedging, which results in expression of different sets of genes (or different levels of gene expression) within different subgroups of cells in the population, thereby generating phenotypic heterogeneity within an otherwise isogenic population. This strategy has been shown to increase the long-term fitness of yeast grown with variable application of either heat shock, “diauxic lag” phase duration, or utilization of different carbon sources (Levy et al 2012; New et al 2014; Wang et al 2015).…”
mentioning
confidence: 99%